2017
DOI: 10.1038/ncomms15271
|View full text |Cite
|
Sign up to set email alerts
|

Tunable and low-loss correlated plasmons in Mott-like insulating oxides

Abstract: Plasmonics has attracted tremendous interests for its ability to confine light into subwavelength dimensions, creating novel devices with unprecedented functionalities. New plasmonic materials are actively being searched, especially those with tunable plasmons and low loss in the visible–ultraviolet range. Such plasmons commonly occur in metals, but many metals have high plasmonic loss in the optical range, a main issue in current plasmonic research. Here, we discover an anomalous form of tunable correlated pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 47 publications
(114 reference statements)
9
58
0
Order By: Relevance
“…The utilization of epitaxial strain is known to be an effective method to modify the symmetry near the interface in a heterostructure (32,33). Although the crystallographic details of the perovskite SrNbO 3 have not been widely studied because of the difficulty of synthesizing the stoichiometric perovskite phase, a recent study with a polycrystal reported the lattice parameters of a = √2a p = 5.6894 Å, b = √2a p = 5.6944 Å, and c = 2a p = 8.0684 Å ( =  =  = 90°) with an orthorhombic structure (space group: Pnma) (34). With a pseudocubic approximation, the lattice parameter a is 4.023 Å (34,35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of epitaxial strain is known to be an effective method to modify the symmetry near the interface in a heterostructure (32,33). Although the crystallographic details of the perovskite SrNbO 3 have not been widely studied because of the difficulty of synthesizing the stoichiometric perovskite phase, a recent study with a polycrystal reported the lattice parameters of a = √2a p = 5.6894 Å, b = √2a p = 5.6944 Å, and c = 2a p = 8.0684 Å ( =  =  = 90°) with an orthorhombic structure (space group: Pnma) (34). With a pseudocubic approximation, the lattice parameter a is 4.023 Å (34,35).…”
Section: Resultsmentioning
confidence: 99%
“…Although the crystallographic details of the perovskite SrNbO 3 have not been widely studied because of the difficulty of synthesizing the stoichiometric perovskite phase, a recent study with a polycrystal reported the lattice parameters of a = √2a p = 5.6894 Å, b = √2a p = 5.6944 Å, and c = 2a p = 8.0684 Å ( =  =  = 90°) with an orthorhombic structure (space group: Pnma) (34). With a pseudocubic approximation, the lattice parameter a is 4.023 Å (34,35). In this work, we grew SrNbO 3 films on latticemismatched SrTiO 3 substrates [a s = 3.905 Å; therefore, the lattice mismatch of (%) = −3.02%] to induce epitaxial strain.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the study of the optical and electronic structures of doped TiO 2 and strontiumniobium oxide have unveiled the presence of resonant excitons at ∼4.6 eV [17] and at ∼4.4 eV [18], respectively, which are very close to Mg II line. The fascinating fact that these resonant excitons can be spectrally tuned via doping or via oxygen control during deposition, respectively, gives a new research direction for the future development of dielectric nanostructured polarizers in this challenging spectral range.…”
Section: Resultsmentioning
confidence: 99%
“…These theoretical studies have predicted that when an effective (U eff ) on-site Coulomb correlation is applied, conventional plasmons might become unconventional ones as plasmonic branches might form, excitations have become very local, and significant spectral weight transfer has occurred. Indeed, unconventional plasmons have been observed in transition metal oxides [3,4]. These observations open new research directions for both fundamental science and the potential to be used in optics and plasmonics, as they have multiple resonances, and are low loss and tunable [4].…”
mentioning
confidence: 98%
“…Indeed, unconventional plasmons have been observed in transition metal oxides [3,4]. These observations open new research directions for both fundamental science and the potential to be used in optics and plasmonics, as they have multiple resonances, and are low loss and tunable [4]. This motivates us to investigate strongly correlated electron systems of layered copper oxides (cuprates) in order to explore an existence of this type of plasmons.…”
mentioning
confidence: 99%